2020
DOI: 10.21037/jtd-20-804
|View full text |Cite
|
Sign up to set email alerts
|

Screening for obstructive sleep apnea with novel hybrid acoustic smartphone app technology

Abstract: Background: Obstructive sleep apnea (OSA) has a high prevalence, with an estimated 425 million adults with apnea hypopnea index (AHI) of ≥15 events/hour, and is significantly underdiagnosed. This presents a significant pain point for both the sufferers, and for healthcare systems, particularly in a post COVID-19 pandemic world. As such, it presents an opportunity for new technologies that can enable screening in both developing and developed countries. In this work, the performance of a non-contact OSA screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Focusing on those which solely use the smartphone without any supplementary external devices, two studies can be extrapolated [ 25 , 26 ]: Regarding the correlation between the snoring time measured by the smartphone compared to the respective gold standard, Nakano et al [ 25 ] revealed a higher correlation than the present study (r = 0.93 versus r = 0.754/0.780). Moreover, both studies [ 25 , 26 ] found also higher correlations comparing the respiratory disturbance indices created by the apps with the AHI obtained by PSG/PG (r = 0.94 [ 25 ] versus r = 0.81 [ 26 ] versus r = 0.495). It has to be kept in mind, that the “Snore Score” calculated by SnoreLab is based on an unknown algorithm and thus cannot be directly compared to specific scores which are associated to respiratory events.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Focusing on those which solely use the smartphone without any supplementary external devices, two studies can be extrapolated [ 25 , 26 ]: Regarding the correlation between the snoring time measured by the smartphone compared to the respective gold standard, Nakano et al [ 25 ] revealed a higher correlation than the present study (r = 0.93 versus r = 0.754/0.780). Moreover, both studies [ 25 , 26 ] found also higher correlations comparing the respiratory disturbance indices created by the apps with the AHI obtained by PSG/PG (r = 0.94 [ 25 ] versus r = 0.81 [ 26 ] versus r = 0.495). It has to be kept in mind, that the “Snore Score” calculated by SnoreLab is based on an unknown algorithm and thus cannot be directly compared to specific scores which are associated to respiratory events.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast to commercial snoring apps, which are available at the common app stores, some research groups developed and tested their own smartphone apps for measurement of snoring and screening of OSA [ 25 , 26 , 35 , 36 ]. Focusing on those which solely use the smartphone without any supplementary external devices, two studies can be extrapolated [ 25 , 26 ]: Regarding the correlation between the snoring time measured by the smartphone compared to the respective gold standard, Nakano et al [ 25 ] revealed a higher correlation than the present study (r = 0.93 versus r = 0.754/0.780). Moreover, both studies [ 25 , 26 ] found also higher correlations comparing the respiratory disturbance indices created by the apps with the AHI obtained by PSG/PG (r = 0.94 [ 25 ] versus r = 0.81 [ 26 ] versus r = 0.495).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scope for prescreening in orthodontic clinics, primary healthcare centers, and hospitals; 6. Automated initial assessment in schools, educational institutions, and driving license authorities; and have been tested previously for screening OSA, including "SleepAp" 9 and "Firefly App," 10 to name a couple of them. However, these are commercial applications that may present cost limitations in a developing country like India.…”
Section: Scope Of the Applicationmentioning
confidence: 99%
“…For example, SleepAp uses actigraphy, position of the body, photoplethysmography, and audio for inputs in a vector machine classifier, as well as a standardized STOP-BANG questionnaire. 9 The "Firefly" app, 10 on the other hand, utilizes AI and advanced digital signal processing (DSP) for identifying stages of sleep, snoring, OSA patterns, and respiration rate. Additionally, the questionnaire used in "SleepAp" 9 has clinical validity only in adults, and hence pediatric OSA cannot be screened, while our mobile application would be applicable for all age groups.…”
Section: Noveltymentioning
confidence: 99%